ANALISIS PENGARUH PERSEPSI OUTLET TERHADAP KREDIBILITAS TENAGA PENJUAL DALAM MENINGKATKAN LOYALITAS OUTLET (Studi Pada Distributor PT. Antar Mitra Sembada Bekasi) - Iwan Kurniawan Subagja (Jurnal Manajemen Bisnis Krisnadwipayana, 2017)
The purpose of this research is to test the influences of salesman characteristic and relationship quality of salesman on outlet trust perception of salesman to increase outlet loyalty. Using these variables, the usage of these variables are able to solve the arising problem within PT. Antar Mitra Sembada Bekasi. The samples size of this research is 100 outlets PT. Antar Mitra Sembada Bekasi. Using the Structural Equation Modeling (SEM). The results show that the salesman characteristic and relationship quality of salesman on outlet trust perception of salesman to increase outlet loyalty. The effect of salesman characteristic on outlet trust perception of salesman are 0,26; The effect relationship quality of salesman on outlet trust perception of salesman are 0,38; and The effect outlet trust perception of salesman on outlet loyalty are 0,43.